Indonesian Rural Healthcare Volunteers’ Knowledge and Practice on Breast Cancer Prevention - Nuridah Nuridah; Yodang Yodang (LLDIKTI Wilayah 1, 2022)
Introduction: Breast cancer has been a new burden and health related issues around the world include Indonesia. The Indonesian Government introduced the cancer care day since the last decade. Healthcare volunteers (HCVs) have been incorporated in the national program under prima health care supervision. The role of HCVs is to assist health care professional and mediate the rural population to actively participate in the health program. This study aims to identify knowledge and practices on breast cancer prevention among rural HCVs. Methods: A cross-sectional study conducted with a total of 52 respondents form a sub-district in Sulawesi Tenggara, rural HCVs, aged 18 years and above, who were recruited voluntarily. Data collection using validated knowledge and practices on breast cancer prevention questionnaires. Results: The participation rate was 65% from total RHCVs, age mean score 35.9 (19-55), all respondents were women, Moslem (90%), was married (86%), and have children (84%), was 90% have an elementary and secondary level of education, and household (80%). Nearly half of the participants have inadequate knowledge on breast cancer prevention. Conclusion: The knowledge and practice among volunteers are remain lack. Study in advance to investigate determinants knowledge and practices on breast cancer program among rural health care volunteers in large sample size is needed.